Using iPS Cells toward the Understanding of Parkinson’s Disease - Torrent, Roger (J Clin Med, 2015)
Cellular reprogramming of somatic cells to human pluripotent stem cells (iPSC) represents an efficient tool for in vitro modeling of human brain diseases and provides an innovative opportunity in the identification of new therapeutic drugs. Patient-specific iPSC can be differentiated into disease-relevant cell types, including neurons, carrying the genetic background of the donor and enabling de novo generation of human models of genetically complex disorders. Parkinson’s disease (PD) is the second most common age-related progressive neurodegenerative disease, which is mainly characterized by nigrostriatal dopaminergic (DA) neuron degeneration and synaptic dysfunction. Recently, the generation of disease-specific iPSC from patients suffering from PD has unveiled a recapitulation of disease-related cell phenotypes, such as abnormal α-synuclein accumulation and alterations in autophagy machinery. The use of patient-specific iPSC has a remarkable potential to uncover novel insights of the disease pathogenesis, which in turn will open new avenues for clinical intervention. This review explores the current Parkinson’s disease iPSC-based models highlighting their role in the discovery of new drugs, as well as discussing the most challenging limitations iPSC-models face today.